ENDORSER SEBAGAI AFFIRMATIVE ACTION DALAM KOMUNIKASI BISNIS - Priyo Dari Molyo (Jurnal Nomosleca, 2016)
Abstract The relevabce between business communications and marketing communications exist is in promotion. Activity is due to both activities related to the increase in profit or gain . Promotion is a middle way between business communication and marketing communication which is achieving the desired target. There is also a strategy that is considered as an act of reassurance to reach the target of endorser use on promotional activities in the media. Use of endorser is not so simple , because a lot of things that must be considered and taken into account in choosing the endorser that communication within the business running effectively and efficiently. Celebrity endorser and experts most suitable for use as a business communication strategy by considering the concept of TEARS. This study uses the methodology of the study of literature that compares several articles to be implemented to the phenomenon in the world of advertising and business communications.DOI : https://doi.org/10.26905/nomosleca.v2i2.621